Identification of angiotensin I converting enzyme inhibitory and radical scavenging bioactive peptides from sea cucumber (Stichopus vastus) collagen hydrolysates through optimization - Abedin, Md. Zainul; Karim, A. A.; Gan, Chee-Yuen; Ghazali, F. C.; Barzideh, Z.; Zzaman, Wahidu; Sarker, Md. Zaidul Islam (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2015)
The sea cucumber (Stichopus vastus) is an underutilized species, as most of its parts, including the integument (high collagen content) are thrown away during processing. The aim of this study was to investigate the effects of different hydrolysis conditions (substrate to enzyme ratio (S/E), reaction temperature, and hydrolysis time) on the angiotensin I converting enzyme (ACE) inhibitory and radical scavenging (RSc) activities of the hydrolysates produced from trypsin hydrolysis of S. vastus collagen. Optimal conditions predicted by Box-Behnken Design modelling for producing ACE inhibitory and RSc hydrolysates were found to be S/E ratio (15), reaction temperature (55°C), and hydrolysis time (1 h). Under optimal conditions, ACE inhibitory and RSc activities were estimated to be as high as 67.8% and 77.9%, respectively. Besides, some novel bioactive peptides were identified through mass spectrometry analysis. These results indicate that S. vastus hydrolysates might be used as a functional ingredient in food and nutraceutical products.